O processo ensino de geografia a partir da hidrografia de Francisco Beltrão – PR - Segala, Fernando José (2017)
To the detriment of the importance of the fulfillment of Environmental Education (AE) teaching and the implementation of methodological practices that approximate the knowledge constructed by the student in the local reality, it was verified through the bibliography researched, among which is indicated Pires (2011) and Biral (2011), which is little linked to EE during the process of Teaching Geography. This assertion corroborates with the hypothesis of the present work that there is underutilization of the knowledge brought by the student about the local space during the teaching process, which would not happen if there was a greater commitment to effect EE practices during the classes, especially Geography. Thus, the present research proposes to investigate how the theme EA and Water Resources (HR) are approached in the High School of Francisco Beltrão - PR and suggest methodologies that link geographic knowledge with the local reality, using as central theme the hydrography of the city. In order to carry out the analysis, two state colleges with differentiated Political and Pedagogical Projects (PPP) were selected to contemplate the realities, both of the students linked to the rural area of the municipality and the urban area. The selected colleges were the Eduardo Virmond Suplicy State College and the Francisco Beltrão - PR Agricultural College (CEEP). The theoretical and bibliographic component of the research was fulfilled by reading and analyzing the State Curricular Guidelines for Geography Teaching (DCES) and the survey of questions related to EE through the research carried out by Guimarães (2006); Smith (1998); Dias (2004); Loureiro (2006); Carson (1962), among others. Research and analysis on how AD and HR are addressed in high school was done through the study of the PPPs of the two colleges; The application of structured questionnaires to 200 (two hundred) students and interviews with six (6) teachers. Through the research, it was concluded that the EE is worked in the schools in an integrated way, but it was also verified that the frequency and depth of the dialogue, especially in the subject of Geography, with the themes of EA and HR, falls short of what the DCEs taken by reference. Based on teachers' suggestions, among them the importance of approaching Geography teaching and EA with an interdisciplinary approach, a recommendation was made for activities that can be used during Geography classes, creating an opportunity for integrated actions In the disciplines from the local HR and making effective the fulfillment of what proposes the curricular structure of the studied colleges.